STUDI PEMANFAATAN CAHAYA ALAM SEBAGAI SUMBER PENCAHAYAAN RUANG KULIAH GEDUNG E KAMPUS âAâ UNIVERSITAS TRISAKTI DALAM RANGKA PENGHEMATAN ENERGI LISTRIK - Irianto, Chaerul Gagarin (Jurnal Teknik Elektro, 2002)
This study is aimed to save electrical energy in buildings by making use ofthe sun light which passes through the windows. The proposed steps are tochange the luminaires so the effective spread light is focused and alteringlight group switch to control the lamps with talking external light intoconsideration.Keywords: side illuminating, glazing, illuminating quality.